PET, MRI, and simultaneous PET/MRI in the development of diagnostic and therapeutic strategies for glioma. Issue 3 (March 2015) - Puttick, Simon; Bell, Christopher; Dowson, Nicholas; Rose, Stephen; Fay, Michael
Graphical abstract: Highlights: PET and MRI play a pivotal role in the development of therapeutic strategies for glioma. Preclinical PET/MRI has the potential to be central to the future of drug development for glioma. PET/MRI allows simultaneous imaging of therapeutic platforms and multiple aspects of cancer. PET/MRI could affect a paradigm shift in the drug development process. Abstract : Glioma is the most aggressive brain tumour, resulting in death often within 1–2 years. Current treatment strategies involve surgical resection followed by chemoradiation therapy. Despite continuing improvements in the delivery of adjuvant therapies, there has not been a dramatic increase in survival for glioma. Molecular imaging techniques have become central in the development of new therapeutic strategies in recent years. The multimodal imaging technology of positron emission tomography/magnetic resonance imaging (PET/MRI) has recently been realised on a preclinical scale and the effect of this technology is starting to be observed in preclinical drug development for glioma. Here, we propose that PET/MRI will play an integral part in the development of new diagnostic and therapeutic strategies for glioma. Teaser: The development of simultaneous PET/MRI imaging technology is poised to reshape drug development in oncology. In this review, we highlight key advances in PET, MRI, and simultaneous PET/MRI that are driving the development of diagnostic and therapeutic strategies for glioma.